Aspiration Pneumonia: Clinical Features, Diagnosis, and Management - Yolanda B. S, Moh. Rizky; Paerdoe, Lalu Dane Pemban; Wardani, Shira Putri; Yulianti, Arwinda Febri; Habib, Philip (Jurnal Biologi Tropis, 2026)
Aspiration pneumonia is a pulmonary infection caused by the inhalation of oropharyngeal secretions, gastric contents, or foreign materials into the lower respiratory tract. It is associated with significant morbidity and mortality, particularly among older adults and patients with neurological disorders. This literature review aims to provide a comprehensive overview of aspiration pneumonia, including its definition, epidemiology, pathophysiology, etiology, clinical manifestations, diagnosis, and management. A literature review was conducted by searching articles published between 2019 and 2025 in the PubMed, Scopus, and Google Scholar databases using the keywords “aspiration pneumonia,” “dysphagia,” “risk factors,” “diagnosis,” and “management.” A total of 15 relevant articles that met the inclusion criteria were selected and analyzed descriptively to summarize current evidence regarding aspiration pneumonia. Aspiration pneumonia occurs when airway protective mechanisms fail, allowing foreign materials to enter the lower respiratory tract. Major risk factors include dysphagia, impaired consciousness, stroke, neurological disorders, and advanced age. Clinical manifestations range from cough, fever, and dyspnea to severe complications such as lung abscess and empyema. Diagnosis is based on clinical history, physical examination, laboratory findings, and radiological imaging. Management depends on disease severity and etiology, including supportive care and appropriate antibiotic therapy. Aspiration pneumonia remains an important clinical condition with substantial health consequences. Early recognition, accurate diagnosis, and appropriate management are essential to improve patient outcomes and reduce complications.